2011
DOI: 10.1089/jwh.2010.1960
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Women and Postpartum Depression

Abstract: Adult VAW is associated with self-reported history of PPD. With an increase in the number of types of abuse experienced, this association became stronger. Our findings highlight the need for thorough VAW screening in obstetrical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 39 publications
4
47
1
3
Order By: Relevance
“…Seven original research papers reported on the association of maternal history of CSA with postpartum depression (Robertson-Blackmore et al 2013) or depressive symptoms (Cohen et al 2002; Roberts et al 2004; Garabedian et al 2011; Plaza et al 2012; Dennis and Vigod 2013). For one study, postpartum information was obtained over email (Bonacquisti et al 2014; personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…Seven original research papers reported on the association of maternal history of CSA with postpartum depression (Robertson-Blackmore et al 2013) or depressive symptoms (Cohen et al 2002; Roberts et al 2004; Garabedian et al 2011; Plaza et al 2012; Dennis and Vigod 2013). For one study, postpartum information was obtained over email (Bonacquisti et al 2014; personal communication).…”
Section: Resultsmentioning
confidence: 99%
“…13 In addition, IPV has been linked to chronic pain, 14 chronic fear and stress states, 15 postpartum depression, 16 substance use, 17,18 cardiovascular disease and hypertension, 19 as well as chronic inflammation 20 and accelerated telomeric attrition. 6 Clearly, the trauma of IPV thus extends well beyond the acutely abusive experience and the provision of traumainformed care to affected individuals is crucial to reducing its impact.…”
Section: Ipv and Healthmentioning
confidence: 99%
“…26 This revision was based in part on findings from studies indicating that women of reproductive age are most at risk for IPV and, clearly, reproductive coercion and that women themselves endorse universal screening. 11,16,23,27,28 In addition to the USPSTF recommendation, many professional organizations endorse IPV screening standards. The American College of Obstetricians and Gynecologists suggests that in addition to routine screening, women presenting for obstetric care should be screened for IPV throughout pregnancy and postpartum.…”
Section: Screeningmentioning
confidence: 99%
“…Childhood sexual abuse is associated with psychiatric symptomatology and pregnancy complications and is reported in up to 37 % of perinatal women (Benedict et al 1999). Physical violence and social isolation in pregnancy also correlate with PPD (Garabedian et al 2011).…”
Section: Introductionmentioning
confidence: 99%